Breath Carbon Monoxide and Semiquantitative Saliva Cotinine as Biomarkers for Smoking - Marrone, Gina F. (2010)
OBJECTIVE: As a biomarker of smoking, semiquantitative analysis of cotinine (NicAlert®) offers several advantages over breath carbon monoxide (CO) and quantitative analysis of cotinine. Recent studies have used urine NicAlert® and breath CO in combination to verify abstinence. However, no studies have evaluated the performance of saliva NicAlert® against or in combination with breath CO. METHOD: Breath CO, saliva NicAlert®, and smoking history were compared in an urban population of daily smokers (n = 24) and nonsmokers (n = 25). RESULTS: Saliva NicAlert® predicted self-reported smoking with 100% sensitivity and 96% specificity. At a cutoff of > 5 ppm, breath CO had 100% sensitivity and 100% specificity in predicting self-reported smoking. Breath CO was positively correlated with saliva NicAlert® and negatively correlated with minutes since last cigarette. CONCLUSION: Saliva NicAlert® had high sensitivity and specificity in identifying daily smokers. Compared to saliva NicAlert®, breath CO level was more indicative of recent smoking. Future treatment studies should evaluate the performance of saliva NicAlert® as an alternative to the urine test.